(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
This work is by no means intended to be a complete study on the subject of judicial minimalism. It is merely the result of an analysis and summary of the study of some interesting articles on the subject, containing the positions of their authors and sometimes adding their own opinions concerning the Brazilian reality. It should be noted that minimalism is a theory developed in the United States of America and vehemently defended by Cass R. Sunstein, a law professor at Harvard University. The main objective of this study is to clearly demonstrate what minimalism really is, according to some interpretations, its intricacies and subdivisions, its applicability and consequences, using examples of concrete cases to better understand the subject. Although this is an American theory or doctrine, where the culture and traditions are very different from Brazil’s, we will try, in the end, to associate cases with our reality.